SERVQUAL ANALYSIS OF CUSTOMERS IN CHOOSING ISLAMIC BANK - Muhammad Nasrullah; Asmuni Asmuni; Saparuddin Siregar; Sri Wahyuni (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to explore and test the perceptions of customers or customers of Islamic banking, especially North Sumatra with Islamic commercial bank offices and their business units regarding Customer Servoual Analysis in Choosing Islamic Banks in a more comparative way. The type used in this research is field research using a quantitative approach through descriptive methods. The results of the study show that the dimensions of perceived service level quality at Islamic banks in North Sumatra are Cartesian diagrams that the influence of service quality consists of: tangible (direct evidence), realiability (reliability), responsiveness (responsiveness), assurance (guarantee), and empathy (empathy). ) on the level of customer satisfaction at Islamic banks studied in North Sumatra, namely BRI Syariah, Mandiri Syariah, BNI Syariah, North Sumatra Syariah, BCA Syariah, Niaga Syariah, Muamalat, and BTN Syariah in terms of tangibles are categorized as very good, reliability is categorized as very good. responsiveness is categorized as sufficient, assurance is categorized as sufficient, and empathy is categorized as very good. And for the five dimensions of service quality, the most dominant variable in service improvement is the tangible variable (direct evidence).Keywords: Servqual, Satisfaction and Customers